Apoptosis induced by damnacanthal from morinda elliptica in T-lymphoblastic leukimia cell line (CEM-SS) - Abdul Hamid, Hisyam (2009)
Current chemotherapy drug showed adverse side effects towards the patients such as vomiting, nausea, constipation, fatigue, muscle pain and other pains. With the high risk of these side effects, majority of cancer patients prefer on finding better cure and lesser side effects. This circumstance somehow urged the scientists to search for alternative medicine, which is natural products that is believed can cure cancer patients with lesser side effects. Such natural product, damnacanthal which is an anthraquinone has been reported to posses inhibitory effects on the cancer promoting ras gene and p561 gene. In a previous study, Damnacanthal from the root of Morinda elliptica was found to induce apoptosis towards the human acute T-lymphoblastic leukaemia cell line (CEM_SS). This study was conducted to determine the mechanisms involved in apoptosis induced by damnacanthal. The cells were treated with 1, 3, 10 and 30 µg/ml damnacanthal and incubated for 24, 48 and 72 hours. Untreated cell were included as control. Following treatment, the samples were subjected to several assays such as cytotoxic study, morphological study, cell cycle analysis and determination of p53, multi caspases (caspase 2, 3, 6, 8 and 9) and Bc12 and Bax proteins activities. The percentage of viable cell at the highest concertration of the compound (30 µg/ml) decreased significantly (p<0.05) after 72 hours to 40.4%. Cells treated with damnacanthal (10 and 30 µg/ml) showed characteristics of apoptosis such as condensation of cytoplasm, membrane blebbing and apoptotic bodies. At the highest concentration of damncanthal (30 µg/ml), the cell cycle was found to be arrested at the G2/M phase after 72 hours incubation. Apoptosis induced by damnacanthal was found to be related to the caspase 2 and caspase 6 activation possibly through p53-independent pathway. In the treatment at higher concentrations of damnacanthal (10 and 30µg/ml), the expression of Bcl-2 protein was down regulated whereas Bax protein was upregulated yet insignificant. Nevertheless, there was a significant correlation of activities between these two proteins. In conclusion, this study indicated that damnacanthal induced cell cycle arrest at G2/M phase most probably through p52-independent pathway and later involved in the activation of caspase 2 and caspase 6, and the downregulation of Bcl2 and upregulation of Bax proteins which are believed drive the cell to undergo apoptosis.